2021
DOI: 10.15408/sjie.v10i2.21451
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Behavioral Intentions to Use Sharia Financial Technology (Fintech)

Abstract: The growth of sharia fintech is not proportional to the majority of the Muslim population. There are only a few studies that discuss the behavioral intentions of consumers who use sharia fintech. This study aims to identify the factors influencing Muslim's behavioral intentions in using sharia fintech. This study conducted 400 respondents in four types of sharia fintech (digital payment, lending, crowdfunding, and risk and management). This study uses a structural Equation Modeling - Partial Least Square (SEM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
5
6
0
2
Order By: Relevance
“…Therefore, analysis of H3 revealed that planned behaviour exerts a positive impact on the intention to adopt Islamic lending Fintech. The result is consistent with previous studies such as Darmansyah et al (2020), Tun-Pin et al (2019, Setiawan et al (2021) found that planned behaviour has a significant impact on encouraging behaviour intentions to use Islamic Fintech.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, analysis of H3 revealed that planned behaviour exerts a positive impact on the intention to adopt Islamic lending Fintech. The result is consistent with previous studies such as Darmansyah et al (2020), Tun-Pin et al (2019, Setiawan et al (2021) found that planned behaviour has a significant impact on encouraging behaviour intentions to use Islamic Fintech.…”
Section: Discussionsupporting
confidence: 92%
“…According to the study's findings, Subjective Norms have a powerful effect on Behavioural Willingness to Invest in the Crowdfunding Platform in Indonesia. This research is similar to previous research (Effendi, Murad, Rafiki, & Lubis, 2020;Setiawan, Darwanto, & Gunanto, 2021), which discovered that the Subjective Norm had a significant and positive impact on the adoption of fintech payments, fintech lending, and sharia crowdfunding. Social norms and the surrounding environment affect a person's perception of adopting financial technology (Chong et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This research showed social influences have a positive and significant impact on behavioral fintech. The results of this study confirmed the research of Setiawan et al, (2021)that information technology in the form of certain applications that a person used and received benefits that met his expectations, the stakeholders would recommend the application to their community. An MSME participant also imitated the use of certain apps used by celebrities, as one of the benefits of social media was related to the availability of financial services (Darmansyah et al, 2020) as well as the smooth running of their business.…”
Section: Table 6 Specific Indirect Effectssupporting
confidence: 78%